The Effect of Storage Conditions on Dimensional Changes of Acrylic Post-Core Patterns - J. Ghanbarzadeh; MR. Sabooni 1; R. Roshan-Nejad (Tehran University of Medical Sciences, 2007)
Objective: The purpose of this study was to evaluate and compare the effect of storage time and conditions on dimensional stability of acrylic patterns. Materials and Methods: In this in vitro study, a cylindrical shaped metallic post-core was fabricated. Impressions were made from this metallic model and 30 samples were prepared with Duralay acrylic resin. The specimens were divided into three groups of ten. Groups A, B and C were stored in dry atmosphere at 25°C; 100% humidity at 25°C; and water placed in the refrigerator at 4°C, respectively. In each sample post length, post diameter and core diameter were measured at baseline, 24 hours and 48 hours after storage. All measurements were performed in an optical measurement device. Data were analyzed using the Rank regression test. Results: The type of dimensional changes seen in this study was shrinkage. A significant difference in post diameter was found between group B and the other two groups (P=0.001). Storing time significantly affected post diameter (P<0.001), but not post length and core diameter. Conclusion: Within the limitation of this study, the best condition for storing Duralay post core patterns was found to be 100% humidity at 25°C for 24 hours. Storage time was also shown to have a negative effect on dimensional stability of Duralay post core patterns, in all three groups.